The Influence of Human Resource Competence and Financial Aspects on the Performance of MSMEs in the Cirendeu Village Area, South Tangerang - Sunarti; Hasanah; Dwi Oktariani; Dio Azril Akbar K; Sururi Afif (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
Along with the development of MSMEs in Indonesia, small and medium enterprises are required to survive in the face of competition. This can trigger MSMEs to create new businesses and be different from other SMEs with better performance. MSMEs have a strategic role in realizing national economic development because MSMEs can absorb labor and contribute to economic growth in Indonesia. According to data from the Ministry of Cooperatives and Small and Medium Enterprises (MSMEs), in 2019 there were 119.6 million workers, an increase of 2.21% compared to the previous year. Many MSMEs lack insight and knowledge so they lack a long-term orientation. Lack of knowledge in the field of management makes efforts to improve performance tend to be conventional. This study aims to determine how the influence of human resource competence on the performance of MSMEs, and the influence of financial aspects on the performance of MSMEs. This research is a comparative causal research which is a research with the characteristics of the problem of a cause and effect relationship between two or more variables. The sample from this study were 30 MSME respondents located in the Cirendeu sub-district. The data analysis used in this study included validity tests, reliability tests, classic assumption tests and partial hypothesis testing (t) with the help of SPSS version 23. The results of this study indicate that HR competence has no significant effect on MSME performance. that the first hypothesis is rejected. The accounting aspect has a significant effect on the performance of SMEs. Accounting knowledge has a smaller significance and t count is greater than t table.